Women Empowerment and The Islamic Perspective: A Review - Irma (SMART Insight, 2022)
This study aimed to analyze the bibliometric characteristics and trends of papers on women empowerment indexed by Scopus from 1994 to 2021. The data were 323 research publications. Data were retrieved from the Scopus database. Bibliometric analysis was conducted using VOSviewer software. This study visualized patterns of the co-occurance keyword by occurance, authors with the highest publications, and institutions with the highest publication related to women empowerment. The results show that the number of studies in the field of women empowerment issue is increased in recent years. Certain keywords, such as women empowerment, Islam, Islamism, and women status, have become the most popular in research period. While the country which most published papers related to women empowerment is Indonesia. Furthermore, Department of Midwifey is the institution which have published most of women empowerment issue. The results showed that research on topic of Women Empowerment continued to increase every year with sub themes that also continued to grow. Further research related to women empowerment in other keywords that have appeared in this bibliometric result are needed to produce more publications in various keywords and discussion.